Achieving Greater Project Success & Profitability through Pre-construction Planning: A Case-based Study. (2016) - Abbas, Ali; Din, Zia Ud; Farooqui, Rizwan
Abstract: Owing to shift in global perspective and socio-economic needs, the construction industry is undertaking risky and complex projects. The complexity of construction projects requires the coordination between designer and contractor in the early stages of the projects. Little research has been performed regarding the pre-construction planning (PCP), which is the integration between contractor and designer in the early stages of a project to ease construction. It is very important for the construction industry stakeholders particularly contractor and designer to acknowledge the significance of PCP. This study analyzed the current utilization of PCP practices, practical benefits from its utilization and barriers faced during its utilization through the study of selected Design-Build residential, commercial infrastructure, transportation, and power plant projects. A questionnaire survey was used for this purpose. The results of this research will provide some solid foundation towards design-construction integration to attain maximum efficiency and success in the construction industry.